PENGARUH PARTISIPASI PENGANGGARAN PADA KESENJANGAN ANGGARAN DENGAN AMBIGUITAS PERAN SEBAGAI VARIABEL PEMODERASI - Ana, Meli Yuli; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi, 2016)
This study aimed to get empirical evidence of the ambiguity of the role as a moderating influence on the budgetary participation BPR budget gap in Denpasar. This study was conducted in 21 rural banks in Denpasar with a survey method using a questionnaire. The number of samples analyzed was 105 respondents using purposive sampling method of sampling. The analysis technique used in this study is Moderated regression analysis (MRA). The research proves that the ambiguity of the role of budgetary participation weakens the negative relationship in RB budget gap in Denpasar. This means that the higher the level of ambiguity of the role that managers who participate in the budgeting process led to increasing budget gap.
Keywords: Participation Budgeting, Budget Gaps, Role Ambiguity